Marker-assisted transfer of leaf and stripe rust resistance from Triticum turgidum var. durum cv. Trinakria to wheat variety HD2932 - Mallick, Niharika; Jha, Shailendra K.; Agarwal, Priyanka; Kumar, Sachin; Mall, Anchal; M, Niranjana; Choudhary, Manish K.; Chandra, Ajay Kumar; Bansal, Shreshtha; Saharan, M. S.; Sharma, J. B.; Vinod, (Frontiers in Genetics, 2022)
A marker-assisted backcrossing program initiated to transfer leaf rust resistance gene LrTrk from Triticum turgidum cv. Trinakria to hexaploid wheat variety HD2932 cotransferred a stripe rust resistance gene, YrTrk, along with LrTrk. The cross of hexaploid recurrent parent HD2932 with tetraploid donor parent Trinakria produced pentaploid F1 plants. F1s were backcrossed with recurrent parent HD2932 to produce BC1F1 generation. Foreground and background selection was conducted in each backcross generation to identify plants for backcrossing or selfing. While foreground selection for LrTrk was carried out with linked and validated molecular marker Xgwm234, for background selection, 86 polymorphic SSR markers from the A and B genomes were used. Single selected plants from BC1F1 and BC2F1 generations backcrossed and selfed to produce BC2F1and BC2F2 generations, respectively. Background selection resulted in 83.72%, 91.86%, and 98.25% of RPG recovery in BC1F1, BC2F1, and BC2F2 generations, respectively. A total of 27 plants with LrTrk in homozygous state were identified in BC2F2 generation and selfed to produce 27 BC2F3 NILs. All the NILs were tested for leaf and stripe rust resistance at the seedling stage using seven Puccinia triticina and one Puccinia striiformis f.sp. tritici rust pathotypes. All the 27 NILs were found to be resistant to both leaf and stripe rust pathotypes. So, these NILs are designated to carry leaf and stripe rust resistance genes LrTrk/YrTrk.